Determinants of Turnover Intention: Job Satisfaction, Employee Retention, Work-Family Conflict and Organisational Commitment - Sari, Selvi Yona; Yenni, Zefri; Aima, M. Havidz (International Review of Management and Marketing, 2024)
This research aims to empirically examine the direct and indirect effects of Work-Family Conflict and Organizational Commitment on Turnover Intention, with Job Satisfaction and Employee Retention as mediating variables. The study employs a quantitative approach. The population comprises permanent employees of PT Bank Nagari in West Sumatra Tbk., with a sample size of 319 employees. The sampling method uses proportional sampling. The analysis method used is partial least squares (PLS) analysis with the SmartPLS application. The results indicate that organisational commitment significantly influences job satisfaction and employee retention. Furthermore, the work-family conflict impacts employee retention. Additionally, work-family conflict, job satisfaction, and employee retention have a significant partial effect on turnover intention. Employee retention mediates the relationship between work-family conflict and turnover intention. Similarly, job satisfaction mediates the relationship between organisational commitment and turnover intention. This research provides suggestions to Bank Nagari to increase employee commitment by providing better support and recognition to increase job satisfaction and employee retention. Then the company must implement policies that support balance between work and family to reduce conflict and increase employee retention.